Supervisi Akademik Kepala Sekolah Dan Pengasuh Pondok Pesantren Dalam Meningkatkan Proses Pembelajaran Pendidikan Agama Islam - Muh Banjari; Lukman Hakim (Al-Mudarris, 2019)
This study aims to determine the method, application, inhibiting factors and supporting academic supervision of principals and caregivers of Islamic boarding schools in improving the learning process of Islamic Education.This study uses a phenomenological qualitative approach. The technique of data collection through documentation and interviews. While the data analysis of this study uses qualitative, inductive.The results of the study concluded that first, the academic supervision of principals and caregivers used a collaborative approach. The supervision technique used two techniques, namely individual and group techniques. Individual techniques include: class visits, observations and individual meetings. Group techniques by holding teacher meetings and training to improve teacher competency. Second, the application of academic supervision is applied to all teachers and staff. Conducted at the beginning of the new school year, every month on a scheduled and unscheduled basis. Third, inhibiting factors include: (a) the time of implementation is not in accordance with the schedule, (b) the health factor of the teacher and supervisor, (c) the social factors of the teacher supervised by the age of the supervisor. Supporting factors include: (a) the teacher's openness factor, (b) the principal and caregiver of the boarding school can control, guide and develop the skills of the teacher, (c) the principal and caregivers of the boarding school are motivated to worship to improve the quality of faithful and devoted human resources.